Challenges in shared decision making in advanced cancer care: a qualitative longitudinal observational and interview study. (16th December 2015) - Brom, Linda; De Snoo‐Trimp, Janine C.; Onwuteaka‐Philipsen, Bregje D.; Widdershoven, Guy A. M.; Stiggelbout, Anne M.; Pasman, H. Roeline W.
Abstract: Background: Patients' preferences and expectations should be taken into account in treatment decision making in the last phase of life. Shared decision making (SDM) is regarded as a way to give the patient a central role in decision making. Little is known about how SDM is used in clinical practice in advanced cancer care. Objective: To examine whether and how the steps of SDM can be recognized in decision making about second‐ and third‐line chemotherapy. Methods: Fourteen advanced cancer patients were followed over time using face‐to‐face in‐depth interviews and observations of the patients' out‐clinic visits. Interviews and outpatient clinic visits in which treatment options were discussed or decisions made were transcribed verbatim and analysed using open coding. Results: Patients were satisfied with the decision‐making process, but the steps of SDM were barely seen in daily practice. The creation of awareness about available treatment options by physicians was limited and not discussed in an equal way. Patients' wishes and concerns were not explicitly assessed, which led to different expectations about improved survival from subsequent lines of chemotherapy. Conclusion: To reach SDM in daily practice, physicians should create awareness of all treatment options, including forgoing treatment, and communicate the risk of benefit and harm. Open and honest communication is needed in which patients' expectations and concerns are discussed. Through this, the difficult process of decision making in the last phase of life can be facilitated and the focus on the best care for the specific patient is strengthened.